1996
DOI: 10.1063/1.116772
|View full text |Cite
|
Sign up to set email alerts
|

Observation of inverse reactive ion etching lag for silicon dioxide etching in inductively coupled plasmas

Abstract: The slowdown of the oxide etch rate with width of submicrometer structures is known as reactive ion etching (RIE) lag and has been explained by ion shadowing and differential charging of the sidewalls, among other effects [R. A. Gottscho and co-workers, J. Vac. Sci. Technol. B 10, 2133 (1992)]. Here we show for an inductively coupled high density plasma reactor working in the pressure regime from 6 to 20 mTorr that inverse RIE lag is primarily observed, i.e., the etch rates increase as the width of the microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
10

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 0 publications
1
30
0
10
Order By: Relevance
“…Radicals may have to undergo several surface collisions in order to reach the bottom of contact holes or trenches. The reduction in radical flux to surface elements at the bottom of features by surface recombination has been discussed extensively, 36,39,107,143 and depends strongly on the value of the recombination coefficient r. This potentially could lead to situations where one location and material may exhibit self-limited adsorption at a monolayer, whereas another material may show multi-layer adsorption. Additionally, the redeposition of etch product on the feature sidewalls has to be considered.…”
Section: Issues and Needsmentioning
confidence: 99%
“…Radicals may have to undergo several surface collisions in order to reach the bottom of contact holes or trenches. The reduction in radical flux to surface elements at the bottom of features by surface recombination has been discussed extensively, 36,39,107,143 and depends strongly on the value of the recombination coefficient r. This potentially could lead to situations where one location and material may exhibit self-limited adsorption at a monolayer, whereas another material may show multi-layer adsorption. Additionally, the redeposition of etch product on the feature sidewalls has to be considered.…”
Section: Issues and Needsmentioning
confidence: 99%
“…1,2 For example, while an ion-neutral synergy model with pure neutral flux shadowing appears to be consistent with a wealth of ARDE measurements in semiconductors, 2 it does not hold for the etching of insulators. Indeed, Doemling et al 3 have reported inverse ARDE of trenches and holes in SiO 2 in a high-density CHF 3 plasma at 20 mTorr. Remarkably, they also reported aspect ratio independent etching ͑ARIE͒ when the pressure was lowered to 6.7 mTorr; for fixed etching time, the etch depth was the same for a variety of trench widths and hole diameters ͑as low as 0.25 m, corresponding to an aspect ratio of 8.5:1͒.…”
Section: ͓S0003-6951͑97͒03930-2͔mentioning
confidence: 99%
“…Even in the best of cases, with an ad hoc exponential dependence of inhibitor flux, they calculated that ARIE should break down at an aspect ratio of Ϸ5:1. Even if the ''magic'' value of the required inhibitor flux was accidentally chosen by Doemling et al, 3 their smallest trench ͑0. 25 m͒ should have been etched less deep than the larger trenches.…”
Section: ͓S0003-6951͑97͒03930-2͔mentioning
confidence: 99%
“…[15,16] This effect, known as RIE lag, ratio features. [17,18] This work investigates the problem of shrinking asymmetric holes uniformly, the physical limitations of depositing in shadowed features, and which plasma parameters can give the best results. There is difficulty in equally shrinking features with very short, confined dimensions with longer dimensions.…”
Section: Introductionmentioning
confidence: 99%